Penerapan Metode Analytical Hierarchy Process dan Additive Ratio Assessment Dalam Menentukan Target Promosi Universitas - Mahendra, Rifqi Gusnar; Trenady, Revangga Alif; Pungkasanti, Prind Triajeng (Building of Informatics, Technology and Science (BITS), 2024)
The Semarang University New Student Admissions (PMB) Department has set a target for the number of new students every year of 4,500 students. To meet this target, the PMB section carries out promotions to several high schools and vocational high schools, however, the PMB section has not yet chosen the school promotion site. apply decision support methods with certain methods that can help select schools for university promotion. This research applies a decision support method with the Analytical Hierarchy Process (AHP) to calculate the weight of each criterion and will continue with ranking calculations using the Additive Ratio Assessment (ARAS) method. The results of applying the AHP method for weighting criteria are: number of school alumni students with a weight of 0.36; the number of active school students was 0.26; the distance between school and university is 0.12; and school-university collaboration of 0.26. From the ARAS ranking method, it was found that SMKN 8 Semarang had the highest score of 0.911; in second place at SMKN 4 Semarang with a score of 0.864; and in third place at SMA Institut Indonesia with a score of 0.823. The aim of this research is to provide better alternative decisions so that it can help the Semarang University PMB section in deciding school promotion targets.